Model-based identification of vadose zone controls on PFAS mobility under semi-arid climate conditions. (15th October 2022) - Wallis, Ilka; Hutson, John; Davis, Greg; Kookana, Rai; Rayner, John; Prommer, Henning
Highlights: Long-term fate of PFAS in the vadose zone was analysed through numerical modelling. Climate-driven physical flow processes can explain observed retention of PFAS in vadose zone. PFAS downward flux confined to short periods of high soil saturation following discrete rain events. Periods of enhanced PFAS downward movement coincide with low air-water interface retention. Sorption to sediments and air-water interface reduce PFAS migration rate by 60%. Abstract: Contamination through per-and poly-fluoroalkyl substances (PFAS) have occurred globally in soil and groundwater systems at military, airport and industrial sites due to the often decades-long periodic application of firefighting foams. At PFAS contaminated sites, the unsaturated soil horizon often serves as a long-term source for sustained PFAS contamination for both groundwater and surface water runoff. An understanding of the processes controlling future mass loading rates to the saturated zone from these source zones is imperative to design efficient remediation measures. In the present study, hydrochemical data from a site where PFAS transport was observed as a result of the decades-long application of AFFF were used to develop and evaluate conceptual and numerical models that determine PFAS mobility across the vadose zone under realistic field-scale conditions. The simulation results demonstrate that the climate-driven physical flow processes within the vadose zone exert a dominating control on the retention of PFAS. Prolonged periods of evapotranspiration exceeding rainfall under the semi-arid conditions trigger periods of upward flux and evapoconcentration, leading to the observed persistence of PFAS compounds in the upper ca. 2 metres of the vadose zone, despite cessation of AFFF application to soils since more than a decade. Physico-chemical retention mechanisms, namely sorption to the air-water interface (AWI) and sediment surfaces, contribute further to PFAS retention. The simulations demonstrate how PFAS downward transport is effectively confined to short periods following discrete rain events when soils display a high degree of saturation. During these periods, AWI sorption is at a minimum. In addition, high PFAS concentrations measured and simulated below the source zone reduce the effect of the AWI further due to a decrease in surface tension associated with elevated PFAS concentrations. Consequently, time-integrated PFAS migration and retardation illuminates that the field-relevant PFAS transport rates are predominantly controlled by the physical flow processes with a lower relative importance of AWI and sediment sorption adding to PFAS retention. Graphical abstract: Image, graphical abstract